2016
DOI: 10.1038/srep32487
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of new diketopiperazines inhibiting Burkholderia cenocepacia quorum sensing in vitro and in vivo

Abstract: Burkholderia cenocepacia, an opportunistic respiratory pathogen particularly relevant for cystic fibrosis patients, is difficult to eradicate due to its high level of resistance to most clinically relevant antimicrobials. Consequently, the discovery of new antimicrobials as well as molecules capable of inhibiting its virulence is mandatory. In this regard quorum sensing (QS) represents a good target for anti-virulence therapies, as it has been linked to biofilm formation and is important for the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 52 publications
0
45
0
1
Order By: Relevance
“…Determination of CepI activity in the presence of BH. B. cenocepacia CepI was expressed in Escherichia coli BL21(DE3) cells and purified according to a previously described procedure (56). The enzymatic activity was determined by a spectrophotometric assay according to Christensen et al (57), which measures the holo-ACP formation by titrating the release of the free thiol of ACP with dichlorophenylindophenol (DCPIP; ϭ 19,100 M Ϫ1 cm Ϫ1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Determination of CepI activity in the presence of BH. B. cenocepacia CepI was expressed in Escherichia coli BL21(DE3) cells and purified according to a previously described procedure (56). The enzymatic activity was determined by a spectrophotometric assay according to Christensen et al (57), which measures the holo-ACP formation by titrating the release of the free thiol of ACP with dichlorophenylindophenol (DCPIP; ϭ 19,100 M Ϫ1 cm Ϫ1 ).…”
Section: Methodsmentioning
confidence: 99%
“…During the last few years, we focused our attention on this topic, proposing new targets, such as the glutamate racemase (Israyilova et al, 2016), new strategies, such as the inhibition of quorum sensing (Scoffone et al, 2016;Buroni et al, 2018) and new drugs (Scoffone et al, 2014), to fight B. cenocepacia infections. We found that the benzothiadiazole derivative C109 is highly effective against B. cenocepacia (Scoffone et al, 2015) and other Gram-negative and-positive bacteria, including Mycobacterium abscessus (Hogan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the development of QS inhibitors as novel drugs to treat bacterial infections has attracted significant attention over the past 20 years (18-21, 23-27, 36). For example, a number of compounds have been screened and identified or synthesized as antagonists of QS systems, including diketopiperazines (37) and baicalein (38). The compounds with activities that interfere with the BDSF QS significantly inhibit B. cenocepacia virulence, suggesting that interference in QS signaling can be used as favorable therapeutic method to treat B. cenocepacia infections.…”
Section: Discussionmentioning
confidence: 99%